Dishonesty not always a ground for dismissal: A comment on the Store (M) Sdn Bhd v Ang Tin Huat & Anor [2016] 9 MLJ 517 - Ali Mohamed, Ashgar Ali (LexisNexis, 2016)
This article discusses primarily the dishonest conduct at the workplace as a ground justifying dismissal, with reference to the case of The Store (M) Sdn BhdvAng Tin Huat & Anor. In this case, it was alleged that the claimant had spent a certain sum of money received from the sale of card box and carton boxes from the supermarket on the dinner for some selected staff of the supermarket to appreciate their sacrifice in success of the branch especially working extended hours during the sales period. He was also alleged to have taken the company's trading stock, 12 bottles of wine, for consumption at the said dinner. The issue before the court was whether the dismissal of the claimant for misusing the company's cash and trading stock on a dinner for some staff without prior approval of the management was excessively harsh, unjust and disproportionate.